2007
DOI: 10.1016/j.vaccine.2007.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic vaccination of rabbits with a ubiquitin-fused papillomavirus E1, E2, E6 and E7 DNA vaccine

Abstract: Previously we showed that intracutaneous vaccination of rabbits with DNA vectors encoding ubiquitin-fused versions of the cottontail rabbit papillomavirus (CRPV) early proteins E1, E2, E6 and E7 protected against subsequent challenge with CRPV. Here we tested the immunotherapeutic activity of a vaccine composed of the four CRPV DNA vectors (designated UbE1267) in rabbits. The results show that the UbE1267 DNA vaccine, relative to empty vector DNA, virtually eliminated papilloma growth in rabbits with subclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…However, E1 immunization has been reported to induce strongly protective immunity and/or papilloma regression [41-44]. E1 has also been tested for therapeutic purposes in previous studies [33, 45-47]. Our study further confirmed that a therapeutic effect could be achieved by E1 targeted immunization for early stage papillomas in rabbits.…”
Section: Discussionsupporting
confidence: 83%
“…However, E1 immunization has been reported to induce strongly protective immunity and/or papilloma regression [41-44]. E1 has also been tested for therapeutic purposes in previous studies [33, 45-47]. Our study further confirmed that a therapeutic effect could be achieved by E1 targeted immunization for early stage papillomas in rabbits.…”
Section: Discussionsupporting
confidence: 83%
“…Improved preventive and therapeutic endpoints have been found in previous studies using combinations of topical treatments and DNA vaccination [45], peptide and DNA vaccines [42], DNA vaccines based on recombinant VSV [44,46] and combinations of multiple antigens [26,35,47]. Adjuvants such as Toll-like receptor agonists and CpG have been included in tumor therapeutic studies to enhance the specific adaptive immunity in hosts [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high immunogenicity, E2 may be considered a target to defeat viral infection in the early or even late stages of disease. A therapeutic vaccine might be effective by inducing E2-specific cytotoxic T cells, as has been tested in the cottontail rabbit PV model by antagonizing experimentally induced viral tumours (Leachman et al, 2002;Brandsma et al, 2007).Further insights into the initial virus infection and tumour progression were obtained by our prospective study, in which L1 and E2 seroreactivity correlated with the outcome of disease. The E2 response was detectable shortly after birth, and it seems that these antibodies mark the early stages of infection.…”
mentioning
confidence: 89%
“…Given the high immunogenicity, E2 may be considered a target to defeat viral infection in the early or even late stages of disease. A therapeutic vaccine might be effective by inducing E2-specific cytotoxic T cells, as has been tested in the cottontail rabbit PV model by antagonizing experimentally induced viral tumours (Leachman et al, 2002;Brandsma et al, 2007).…”
Section: Analysis Of the Serological Response Against Mnpv Andmentioning
confidence: 99%